Dakwah Melawan Globalisasi - Syuafa'at Syufa'at (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2008)
Da'wa hos two missions, namely keilohion and kerisolohon. The mission of keilohion means to free human beings from spiritual slavery while the  mission of kerisolohon means to free human beings and invite them to commit good deed and avoid bod deed. It also invites human beings to believe in Allah (QS 3:110). In this globalization era, da'wa faces some threats, such as theological, spiritualistic, and global threats. emergence of , and sobilisosi The first includes  oqidoh destruction through pluralism issue, the. The second threat includes the real condition now that there ore many people who hove great devotion to do rituals  such as salat, haji, but at the some time they a/so do some corruption and other bad tricks. The third threat includes the issue of terrorism, global worming, gender, human right, sex tourism, and so on. As a result, critical interpretation is neededto  face globalization issues so that do'wo will sorvive and function as rahmatan Iii 'alamin.